Exploring mechanical property balance in tufted carbon fabric/epoxy composites. - Dell'Anno, Giuseppe; Cartié, Denis D. R.; Partridge, Ivana K.; Rezai, Amir (Elsevier Science B.V., Amsterdam., 2007)
The paper details the manufacturing processes involved in the preparation of through-the-thickness reinforced composites via the ‘dry preform–tufting–liquid resin injection’ route. Samples for mechanical testing were prepared by tufting a 5 harness satin weave carbon fabric in a 3 mm × 3 mm square pitch configuration with a commercial glass or carbon tufting thread, infusing the reinforced preforms with liquid epoxy resin and curing them under moderate pressure. The glass thread reinforcement increases the compression-after-impact strength of a 3.3 mm thick carbon fabric laminate by 25%. The accompanying drop- downs in static tensile modulus and strength of the same tufted laminate are below 10%. The presence of tufts is also shown to result in a significant increase in the delamination crack growth resistance of tufted double-cantilever beam specimens and has been quantified for the case of a 6 mm thick tufted carbon non-crimped fabric (NCF)/epoxy c
Keywords: 3-Dimensional reinforcement; Polymer matrix composites (PMCs); Preform